Investigating the effects of dietary and management modifications on Salmonella enterica population in harvest-ready beef cattle - Yesica Botero; Kasi Schneid; Kendall L. Samuelson; John T. Richeson; Ty E. Lawrence; Gizem Levent (Microbiology Spectrum)
ABSTRACT Salmonella enterica, a foodborne pathogen, poses a significant public health risk, particularly because of multidrug-resistant strains. Cattle are one of the known reservoirs of Salmonella that contaminates beef products. Whereas antibiotic use in cattle contributes to the selection of antibiotic-resistant strains, it is essential to understand other factors that may influence Salmonella dynamics in cattle and their feedlot environment to mitigate and control related public health risks effectively. With this double-blinded, randomized controlled feedlot study, originally designed to evaluate the effects of dietary (high-starch vs. low-starch) and feeding management (erratic vs. regular feeding) changes on animal performance and liver abscess formation, we aimed to investigate Salmonella prevalence and antibiotic susceptibility profiles in cattle and the feedlot during the approximately 222-day-long feeding period and at harvest. Fecal, hide, lymph node, and soil samples were collected from study cattle, resulting in 863 fecal samples, 309 hide swabs, 131 lymph nodes, and 288 composite pen samples. Salmonella was isolated using standard methods involving non-selective and selective media. Among the 536 isolates tested for phenotypic antibiotic susceptibility, two soil-origin isolates recovered during the feeding period were antibiotic-resistant and likely did not remain persistent due to a lack of selective pressure. Overall, treatments did not affect (P > 0.05) Salmonella prevalence in cattle feces, hides, or the feedlot environment. However, the high-starch diet demonstrated potential as a pre-harvest intervention, reducing Salmonella prevalence by 0.20 (95% CIs 0.02–0.43) in cattle lymph nodes, which may help mitigate and control Salmonella risks in beef products.IMPORTANCESalmonella is a leading foodborne pathogen, causing numerous infections, hospitalizations, and deaths annually in the United States. Cattle are known to harbor Salmonella; therefore, understanding factors influencing Salmonella dynamics in cattle and the feedlot environment is essential to mitigate or control associated risks in beef products. Here, we investigated the effects of dietary energy (high-starch vs. low-starch diet) and feeding management (regular vs. erratic feeding) on Salmonella in cattle and the feedlot environment. Our findings suggest that a high-starch diet may have the potential to reduce Salmonella prevalence in cattle lymph nodes, a potential source of Salmonella outbreaks. In addition, most Salmonella isolates were pansusceptible, with only a few antibiotic-resistant strains identified, which were likely not persistent due to a lack of selective pressure. Further research is needed to evaluate the use of a high-starch diet as a pre-harvest intervention to control and mitigate Salmonella risks in final beef products.